2013
DOI: 10.1039/c3nr03707j
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles and fluorescently-labelled DNA as a platform for biological sensing

Abstract: In the past decade gold nanoparticle-nucleic acid conjugates became progressively important for biomedical applications. Fluorophores attached to nucleic acid-gold nanoparticle conjugates have opened up a new era of biological sensing. The most promising advancement in this field was the invention of the so-called 'nano-flare' systems. These systems are capable of detecting specific endocellular targets such as mRNAs, microRNAs or small molecules in real time. In this minireview, we discuss the current progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 80 publications
0
57
0
Order By: Relevance
“…Gold nanoparticles coated with a shell of oligonucleotides (SNAs) have been successfully used for live cell mRNA detection coupled with targeted delivery of therapeutic agents, opening up new possibilities for the successful treatment of cancer. [11,12] Gold nanoparticles can also be successfully functionalized with peptides. It has been shown that peptide conjugation can result in highly active anti-angiogenic therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles coated with a shell of oligonucleotides (SNAs) have been successfully used for live cell mRNA detection coupled with targeted delivery of therapeutic agents, opening up new possibilities for the successful treatment of cancer. [11,12] Gold nanoparticles can also be successfully functionalized with peptides. It has been shown that peptide conjugation can result in highly active anti-angiogenic therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of nanomaterials with functional DNA has provided new hybrid systems (Rosi and Mirkin, 2005). Among various nanomaterials, gold nanoparticles (AuNPs), with huge reactive surface area, unusual catalytic property and biocompatibility, were often used to prepare aptamer-conjugated AuNPs for detection of biomolecules Deng et al, 2013;Jungemann et al, 2013). And the formed DNA-AuNP conjugates have been utilized as amplifying labels for novel biosensing protocols owning to their unique physical and chemical features, such as multivalent binding capability, enhanced affinity, excellent catalytic properties for signal amplification (Qiu et al, 2013;Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] An important property of AuNP-DNA conjugates is their ability to bind complementary nucleic acids with a high affinity through Watson-Crick base pairing. 1,2 In recent years this property has led to the development of probes to visualise and detect -in the live cell, at real time-cell to cell variations in messenger RNA (mRNA) expressions. 1,[19][20][21][22][23][24][25][26] Research groups led by Mirkin and Alivisatos were the first to report that spherical AuNPs could be functionalised with oligonucleotide strands.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In recent years this property has led to the development of probes to visualise and detect -in the live cell, at real time-cell to cell variations in messenger RNA (mRNA) expressions. 1,[19][20][21][22][23][24][25][26] Research groups led by Mirkin and Alivisatos were the first to report that spherical AuNPs could be functionalised with oligonucleotide strands. 16,17 AuNPs functionalised with DNA have shown great promise as building blocks to form organized structures due to DNA's inherent specificity of molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation